Synthesis and Antibacterial Activity of Some 2-Acetamido-4-[2’-(2", 6" -dinitro-4" -trifluoromethylphenoxy )-5’ -methylphen-1’-yl]-6-substituted phenyl Pyrimidines. - MODl, S.R.; JAHANGIRPURIA, H.D.; PATEL, M.R.; NAIK., H.B. (Asian Journal of Chemistry, 2010)
2-Acetamido-4-[2´-(2",6"-dinitro-4" -trifluoromethyl phenoxy)5´-methylphen-1´-yl]-6-substitutoo phenyl pyrimidines have been synthesised by the acetylation of 2-amino-[2´-(2",6"-dinitro-4"-trifluoromethylphenoxy)-5´-methylphen-1´-yl]-6-substituted phenylpyrimidines with acetic anhydride. These compounds were screened for antibacterial activity against S. aureus and E. coli.